Pengembangan Buku Bujang Dare Anti Perundungan Untuk Siswa Sekolah Dasar Di Kota Pontianak Sebagai Edukasi Bahaya Perundungan - Dyoty Auliya Vilda Ghasya; Kartono Kartono; Nanny Safrianty; Bayu Prasodjo; Ahmad Yani T (STKIP Singkawang, 2025)
This research aims to develop a book aimed at elementary school students as education about the dangers related to bullying. This book contains educational content about bullying in the school environment. The research method used is development research. The data needed in research on the development of the book